Cultural influences on adherence to cardiac rehabilitation programmes: perspectives from South Asian healthcare professionals. (2nd November 2022) - Ahmed, Farhin; Eberhardt, Judith; van Wersch, Anna; Ling, Jonathan
Abstract : Background/Aims: Health disparities concerning uptake of and adherence to cardiac rehabilitation post-myocardial infarction have been observed in patients with coronary heart disease from a South Asian background. Healthcare professionals from a South Asian background can provide insight into the influential cultural factors affecting cardiac rehabilitation adherence. The aim of the study was to explore cultural factors impacting adherence to cardiac rehabilitation post-myocardial infarction from the perspective of healthcare professionals from a South Asian background. Methods: A qualitative thematic approach using semi-structured interviews was employed with 15 participants (8 men and 7 women) recruited from various healthcare settings. The participants were from a range of health professions, including a physiotherapist, general practitioner, nurse, surgeon, physiologist, cardiologist and pharmacist. Results: Four themes were identified from the interviews: familiarity: influence of practitioners' own cultural background; Western vs Eastern medical philosophy: generation and gender influences; engaging with existing services: changing patients' attitudes and perceptions; and modifying practitioner–patient communication: encouraging patient responsibility. All themes related to health beliefs that patients from a South Asian background were perceived to hold. Conclusions: Previous research has suggested that there is a need to tailor health services towards people from a South Asian background. However, the focus should also simultaneously be on changing patients' perceptions of their own health and to consider providing outpatients with the support to develop the necessary skills to implement lifestyle changes towards improving cardiac rehabilitation uptake and adherence.